2009
DOI: 10.1038/ejcn.2008.79
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of calcium-vitamin D3 fortified milk on blood pressure and serum lipid concentrations in healthy older men

Abstract: Background/Objectives: Some epidemiological and clinical studies have shown that increased dairy consumption or calcium and/or vitamin D supplementation can have a beneficial effect on blood pressure, and lipid and lipoprotein concentrations. The aim of this study was to assess the long-term effects of calcium-vitamin D 3 fortified milk on blood pressure and lipid-lipoprotein concentrations in community-dwelling older men. Subjects/Methods: This is a substudy of a 2-year randomized controlled trial in which 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 41 publications
1
25
1
Order By: Relevance
“…The isolated decrease in systolic BP among the vitamin D group at 5 months' follow-up is most likely a chance finding, because this small difference was not observed at 18 months (Table 3), although we cannot rule out a short-term true effect over several months during winter when the 25(OH)D 3 difference (74 nmol/L) between comparison groups was highest (Table 2). These results confirm previous studies of long-term supplementation (≥1 year), which have reported either no effect of vitamin D supplementation on BP 14,15,[28][29][30][31][32] or an increase in systolic BP in participants given 20 000 IU per week. 32 We think the latter is probably a chance finding because there was no change in systolic BP among participants given 40 000 IU per week.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The isolated decrease in systolic BP among the vitamin D group at 5 months' follow-up is most likely a chance finding, because this small difference was not observed at 18 months (Table 3), although we cannot rule out a short-term true effect over several months during winter when the 25(OH)D 3 difference (74 nmol/L) between comparison groups was highest (Table 2). These results confirm previous studies of long-term supplementation (≥1 year), which have reported either no effect of vitamin D supplementation on BP 14,15,[28][29][30][31][32] or an increase in systolic BP in participants given 20 000 IU per week. 32 We think the latter is probably a chance finding because there was no change in systolic BP among participants given 40 000 IU per week.…”
Section: Discussionsupporting
confidence: 91%
“…However, previous studies have failed to detect a differential effect of vitamin D on either BP measure. 13,15 All previous long-term supplementation studies, 14,15,[28][29][30][31][32] including our own, have enrolled mainly participants of European ancestry (ie, white race). It is possible that vitamin D could lower BP in other specific race/ethnic groups, as observed in an Iranian study that supplemented with fortified yoghurt for 12 weeks 23 and in a recent study of blacks supplemented for 3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 However, there was also a greater reduction in energy intake in cereal diet that was due to a ~1,000 kJ greater initial intake, which may also have contributed to the greater weight loss. 23 While vitamin D intake was increased, it was still suboptimal and the differences were seen over a short time-frame of only 26,27 One study found no differences in weight changes between the groups, 26 and the other found weight significantly increased by 1.0 kg in the milk group compared with the nonmilk group and there was a trend for a greater increase in fat mass of 0.6 kg. 27 The milk group in the second study also significantly increased their energy compared with no change in the other groups (+846 kJ/day), which could have impacted on the weight gain.…”
Section: Increases In Vitamin D Through Fortified Foods and Seasonsmentioning
confidence: 99%
“…28 25OHD levels were not measured, so they were not able to determine if the fortified products improved vitamin D status or if it was other parts of the intervention that were having the beneficial impact. In the majority of these studies the participants were vitamin D sufficient at baseline [25][26][27] that, along with the low dose of vitamin D in the fortified products, could also have accounted for a modest increase in 25OHD levels. In some studies the products led to differences in energy intake that could have influenced subsequent weight loss and the products fortified with vitamin D and calcium.…”
Section: Increases In Vitamin D Through Fortified Foods and Seasonsmentioning
confidence: 99%